Determinants Of Mental Health Disorders During The COVID-19 Pandemic - Ari Kresna Dewi, Ni Luh Gede; Yusuf, Ah; Tristiana, Roro Dian (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2022)
Introduction:Many people experienced mental health disorders due to the Covid-19 pandemic and if not treated immediately, it will cause serious problems. The aim of this article was to determine the determinants of mental health disorders during a pandemic. Method :A systematic approach in this review used the PRISMA approach and journal sources from several databases including Scopus, Science Direct, SAGE, NCBI, ProQuest in the 3 last years from 2020 to 2022. Boolean operators within search process used AND and OR. The inclusion criteria were the general public, aged more than 17 years. Exclusion criteria were people with chronic disease and schizophrenia. Literature review, editorial, critical synthesis, and the like were also exclusion criteria for this review. Results: Overall, this review consisted of 13 articles and all of article designs were cross sectional. Respondents in all articles were the general public, the age of 17-60 years. The determinant of mental health disorders were female gender, older age, history of chronic diseases, exposure to media reporting COVID-19, education, job loss and marital status, especially those who were married. Conclusion: Overall, the community experienced mental health problems during the pandemic. Keywords : determinants; factors; mental health disorders; covid-19